Жаңартылған білім беру мазмұны жағдайында оқушылардың өз оқу әрекетін бақылауы (Journal of Educational Sciences, 2020)
of a school chemistry course shows the possibility of using a technological map as one of the methodsfor organizing students’ self-control over their educational activities.Based on the data of the pedagogical experiment, in which 52 students from Almaty schools participated,it was proved that the methods of self-control in learning positively affect the quality of learningoutcomes in chemistry, which is associated with self-control of students over educational activities inchemistry in high school.Key words: quality of education, sustainable development, educational activities, self-control, technologicalmap, content of updated education, assessment.